Enhancement of biogas production from food waste and sewage sludge – Environmental and economic life cycle performance. (15th June 2016) - Eriksson, Ola; Bisaillon, Mattias; Haraldsson, Mårten; Sundberg, Johan
Abstract: Management of municipal solid waste is an efficient method to increase resource efficiency, as well as to replace fossil fuels with renewable energy sources due to that (1) waste to a large extent is renewable as it consists of food waste, paper, wood etc. and (2) when energy and materials are recovered from waste treatment, fossil fuels can be substituted. In this paper results from a comprehensive system study of future biological treatment of readily degradable waste in two Swedish regions are presented. Different collection and separation systems for food waste in households have been applied as well as technical improvements of the biogas process as to reduce environmental impact. The results show that central sorting of a mixed fraction into recyclables, combustibles, biowaste and inert is a competitive option compared to source separation. Use of pellets is beneficial compared to direct spreading as fertiliser. Fuel pellets seem to be the most favourable option, which to a large extent depends on the circumstances in the energy system. Separation and utilisation of nitrogen in the wet part of the digestion residue is made possible with a number of technologies which decreases environmental impact drastically, however to a substantial cost in some cases. Highlights: Central sorting is competitive compared to source separation. Use of digestate pellets is beneficial compared to direct spreading as fertiliser. Fuel pellets is most beneficial due to the circumstances in the energy system. Using nitrogen in wet digestate decreases environmental impact drastically. Using nitrogen in wet digestate has a substantial cost in some cases.